A simple and efficient approach to fabricate graphene/CNT hybrid transparent conductive films. Issue 83 (14th November 2017) - Zhang, Jianhua; Chen, Zhangfu; Xu, Xiaoxue; Liao, Wei; Yang, Lianqiao
Abstract : In this paper, a novel and scalable method to fabricate graphene/carbon nanotube (CNT) hybrid transparent conductive films on Cu substrates, which combines electroplating and chemical vapor deposition (CVD) is proposed and demonstrated. Abstract : In this paper, a novel and scalable method to fabricate graphene/carbon nanotube (CNT) hybrid transparent conductive films on Cu substrates, which combines electroplating and chemical vapor deposition (CVD) is proposed and demonstrated. The Cu substrate was electroplated with electrolyte containing conductive CNTs; then, a uniform graphene film was grown on Cu. After a commonly utilized polymethyl methacrylate assisted transfer process, a hybrid graphene/CNT transparent conductive film was obtained at the target substrate. Conventional graphene grown on electropolished Cu was used as the reference sample. The comprehensive characterization using scanning electron microscopy (SEM), Raman microscopy system, and transmission electron microscopy (TEM) selected area electron diffraction pattern show that the CNTs are uniformly covered by a monolayer graphene with comparable quality to graphene grown on electropolished Cu. The hybrid thin films exhibit outstanding surface morphology (RMS of 1.26), obviously enhanced electrical properties (the square resistance decreases from 490 to 394 Ω sq −1 ), better surface wettability (7° decrease in contact angle), and a negligible transmittance loss (1.3% reduction at 550 nm) compared to CVD graphene that was grown on electropolished Cu. It is anticipated that the graphene/CNT hybrid films that are fabricated using the proposed approach can be a promising alternative to ITO to realize the emerging, particularly flexible optoelectronic devices.